P29 Use of pedometers as a tool to promote daily physical activity levels in patients with chronic obstructive pulmonary disease: a systematic review and meta-analysis. (12th November 2019) - Armstrong, M; Winnard, A; Chynkiamis, N; Boyle, S; Burtin, C; Vogiatzis, I
Abstract : Introduction: Interventions to promote daily physical activity are becoming important in the management of patients with COPD due to significantly lower levels of physical activity compared to healthy age-matched controls [1]. To-date inconsistent findings surrounding the implementation of physical activity promotion and the way pedometers are used have been reported. Objective: To systematically determine aspects of physical activity promotion, including how pedometers are used to optimise daily physical activity in COPD patients. Methods: A Systematic review-meta analysis of prospective studies reporting pedometer physical activity promotion in patients with COPD was performed using: Medline/Pubmed, Cochrane library, Web of science and CINAHL databases. Based on this search, the standard mean difference (SMD) of steps/day were pooled in a random-effects meta-analysis. Results: Of 2582 articles identified, 55 were reviewed in detail and 17 were included, involving 1677 patients. Daily physical activity was improved with pedometer physical activity promotion as a standalone intervention (SMD 0.53; 95% CI: 0.29, 0.77; n=12), and alongside pulmonary rehabilitation (SMD 0.51; 95% CI: 0.13, 0.88; n=7). Additional subgroup analyses found comparable improvements in daily physical activity among studies which provided: i) weekly or infrequent goal setting, ii) an intervention length less or more than 3 months, iii) remote or face-to-face contact (figure 1). Patients benefited more from physical activity promotion when baseline levels of physical activity were greater than 4000 steps/day and when physical activity was reported using a pedometer opposed to an accelerometer (figure 1). Conclusions: Pedometer use is effective in inducing meaningful improvements in daily physical activity [2] in COPD both alongside pulmonary rehabilitation and as a standalone intervention. Future studies should investigate the effectiveness of combining pulmonary rehabilitation and physical activity promotion in patients with profoundly low activity levels and those experiencing anxiety and depression. References: Pitta F, et al . Characteristics of physical activities in daily life in chronic obstructive pulmonary disease. American Journal of Respiratory and Critical Care Medicine 2005;171(9):972–977. Demeyer H, et al . The minimal important difference in physical activity in patients with COPD. PLoS One 2016;11(4):e0154587.